2020
DOI: 10.37358/rc.20.9.8337
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subgroups of Endometrial Carcinoma in Romanian Patients

Abstract: Molecular classification of endometrial carcinoma (EC) has represented a breakthrough ever since the TCGA (The Cancer Genome Atlas) project published it in 2013. Four distinct molecular subgroups were recognized based on somatic copy number alterations and tumor mutational burden: POLE (polymerase-epsilon) ultramutated, MSI (microsatellite instability) hypermutated (MSI-H), copy number low (CNL) and copy number high (CNH). However, implementing a standardized algorithm in current practice is far from being def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It has also been documented that increased TME induces PD-1/PD-L1 mediated fluctuating immune resistance, which usually leads to aggressive tumour phenotype and a poor prognosis. In our study, PD-L1 expression was highly correlated with this subgroup that additionally showed other unfavourable prognostic parameters: younger age, higher FIGO grade, deep myometrial invasion, tumour size, and positive LVSI 7 . Similar results were found in other studies 21 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has also been documented that increased TME induces PD-1/PD-L1 mediated fluctuating immune resistance, which usually leads to aggressive tumour phenotype and a poor prognosis. In our study, PD-L1 expression was highly correlated with this subgroup that additionally showed other unfavourable prognostic parameters: younger age, higher FIGO grade, deep myometrial invasion, tumour size, and positive LVSI 7 . Similar results were found in other studies 21 .…”
Section: Discussionsupporting
confidence: 60%
“…The samples of endometrial carcinomas were reviewed, cored (1 mm) in triplicate and arrayed as previously described 7 . Tissue microarray (TMA) sections were stained with antibodies against CD4 (Ventana, catalogue number 790-4423, clone SP35, Rabbit), CD8 (Ventana, catalogue number 790-4460, clone SP57, Rabbit), CD68 (Ventana, catalogue number 790-2931, clone KP-1, Mouse) and PD-L1 (Ventana, catalogue number 790-4907, clone SP263, Rabbit).…”
Section: Methodsmentioning
confidence: 99%
“…The cases selection was performed from a previous database 7 and included 50 cases of ECs from the Pathology Department archives, diagnosed between 2014 and 2019. Molecular classification for ECs was already performed and divided the cohort into four subgroups: MSS subgroup, MSI subgroup, p53abn subgroup and p53wt subgroup 7 . In addition, Programmed Death -Ligand 1 (PD-L1) testing was assessed on this cohort 8 .…”
Section: Methodsmentioning
confidence: 99%
“…The obtained samples of endometrial carcinoma were reviewed, cored (1mm) in triplicate and arrayed as previously described 7 . Tissue sections were stained with antibodies against -catenin (Ventana, catalogue number 760-4242, clone 14, Mouse) and protocol was followed for staining.…”
Section: Methodsmentioning
confidence: 99%